Laparoscopic management in hydatid disease of liver: a series of 35 cases - Shaikh, Aftab S.; Tandur, Amarjeet E.; Pathrabe, Yugal S.; Patil, Dhiraj S.; Bhandarwar, Ajay H.; Shaikh, Nilofar A. (International Surgery Journal, 2021)
Background: The purpose of this study is to analyse the sociodemographic factors & clinical features of hydatid disease of liver and to emphasize on the safety, efficacy and the role of laparoscopy in its management in the present scenario. Methods: A prospective observational study was done for 35 patients who were diagnosed with and later underwent surgical intervention laparoscopically for hydatid disease of liver over a duration of 3 years from January 2017 to December 2019. Diagnosis was based on the history, clinical examination, ultrasonography of abdomen (USG) and contrast enhanced computed tomography scan of abdomen (CECT). Results: A slight female preponderance with most cases in the 4th decade of life and belonging to rural areas and low socio-economic status. A single cyst in the right lobe of the liver was most common lesion. The most common surgery performed was laparoscopic de-roofing of the cyst with omentoplasty. The most common complication was intra-operative spillage of cyst contents followed by post-operative biliary leak. Conclusions: In the present era laparoscopic surgery is safe, efficacious and plays a crucial role in the management of hepatic hydatid disease with its proven benefits over the conventional surgeries including less morbidity and mortality and reduced rate of recurrence.